Lanthanide [terbium(III)]-doped molecularly imprinted nanoarchitectures for the fluorimetric detection of melatonin - Özgür, Erdoğan; Patra, Hirak K.; Turner, Anthony P. F.; Denizli, Adil; Uzun, Lokman (American Chemical Society, 2020)
Polymerizable terbium(III) complex-based fluorescent molecular imprinted smart nanoparticles were synthesized for the quantitative determination of potential metabolic destitution biomarkers. Melatonin has been reported to be one of the key factors in seasonal affective disorder (SAD) and was chosen as a model metabolite to demonstrate a novel molecularly imprinted polymer (MIP) nanoparticle sensor. We exploited lanthanide ion complexes in our biosensing platforms due to their deeper penetration ability, negligible autofluorescence, lack of photobleaching and photoblinking, and their sharp absorption and emission bands, extreme photostability, and long lifetime. Given the high affinity of lanthanide ions for carboxylic acid groups, we used two amino acid-based functional monomers, N-methacryloyl-l-tryptophan and N-methacryloyl-l-aspartic acid, to coordinate terbium(III) ions and melatonin, respectively. The fluorescent MIP nanoparticles were synthesized using a miniemulsion polymerization technique after forming complexes between terbium(III):MA-Asp and melatonin:MATrp molecules. Due to the polymerizability of lanthanide complexes, they were readily inserted into the polymeric chain, which enabled homogeneous distribution as well as closer orientation to the imprinted cavities for selective melatonin recognition.
Keywords: Lantanite ions; molecular imprinting; fluorescent molecular imprinted nanoparticles